Manajemen Arsip Dinamis Dalam Meningkatkan Akuntabilitas Sekolah - Mar’atus Sholikah; Febrika Yogie Hermanto (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2021)
Record is one of the most fundamental components of school accountability. This study aims to investigate and explain how dynamic record management can improve school performance accountability. Qualitative descriptive with an interactive model was a kind of research that we used. Collecting data through techniques of observation, interviews, and documentation. Data analysis includes reduction, display, and conclusion. The number of informants is 3 archivists, 11 users, and one of the record experts. Finding of this study proves that the application of dynamic record management is able to improve school accountability. Some constraints in dynamic record management are the lack of human resources in the record field. Moreover, the facilities and infrastructure are still not adequate, and the system of record storage has not been consistent. Furthermore, the maintenance record can provide the authentic document in arranging the report of performance and accountability, because the maintenance record is able to save the physical record.